Pyrazolo Derivatives as Potent Adenosine Receptor Antagonists: An Overview on the Structure-Activity Relationships. (7th March 2011) - Cheong, Siew Lee; Venkatesan, Gopalakrishnan; Paira, Priyankar; Jothibasu, Ramasamy; Mandel, Alexander Laurence; Federico, Stephanie; Spalluto, Giampiero; Pastorin, Giorgia
Abstract : In the past few decades, medicinal chemistry research towards potent and selective antagonists of human adenosine receptors (namely, A1, A2A, A2B, and A3 ) has been evolving rapidly. These antagonists are deemed therapeutically beneficial in several pathological conditions including neurological and renal disorders, cancer, inflammation, and glaucoma. Up to this point, many classes of compounds have been successfully synthesized and identified as potent human adenosine receptor antagonists. In this paper, an overview of the structure-activity relationship (SAR) profiles of promising nonxanthine pyrazolo derivatives is reported and discussed. We have emphasized the SAR for some representative structures such as pyrazolo-[4, 3- e ]-1, 2, 4-triazolo-[1, 5- c ]pyrimidines; pyrazolo-[3, 4- c ] or -[4, 3- c ]quinolines; pyrazolo-[4, 3- d ]pyrimidinones; pyrazolo-[3, 4- d ]pyrimidines and pyrazolo-[1, 5- a ]pyridines. This overview not only clarifies the structural requirements deemed essential for affinity towards individual adenosine receptor subtypes, but it also sheds light on the rational design and optimization of existing structural templates to allow us to conceive new, more potent adenosine receptor antagonists.